The Leadership Styles of Nelson Mandela as a Pattern for African Leaders - Isaac I. Akuva, D. G. & (2020) (Covenant University Journal of Politics and International Affairs, 2020)
The paper discusses the leadership style of Nelson Mandela as a model for African leaders in a bid to addressing the challenge of leadership crisis in African. While secondary data was used to support the arguments in the paper, content analysis was used to analyze the data. The findings of the paper show that, Nelson Mandela was a selfless humanist anti-apartheid revolutionist who stood for equality, justice, peace and freedom. It was also found that Mandela was not power amok like other African leaders, Mandela’s insistence not to be in office for more than four years as the President of South Africa, his determination, spirit of forgiveness and willingness for reconciliation, were discovered to be responsible for Mandela’s exceptional leadership style in Africa. In the conclusion it is argued that the leadership style of Mandela was undoubted responsible for him being a leader par excellence in Africa. It is recommended that African leaders should be willing to immolate the leadership style of Mandela in order to resolve the leadership crises in Africa. If the African Union does not rise fast to promote the leadership style of Nelson Mandela among African leader, the continent will continue to experience the crisis of leadership that produces underdevelopment.